Bidding Law - The National Assembly (2005)
This Law provides for bidding activities to select suppliers of consultancy services or goods or construction and installation contractors: Development investment projects with 30% of its capital originating from the state budget; State budget-funded projects for procurement of assets to maintain regular operations of state agencies, political organizations, socio-political organizations, socio-political-professional organizations, social organizations, socio-professional organizations or people's armed forces units; State budget-funded projects for procurement of assets in service of renovation or overhaul of already invested equipment, production chains, works or workshops of state enterprises